Healthcare workers’ perspectives on trauma and mental health access for Rohingya refugees in Cox’s Bazar - Lindsey Green; Linda Kaljee; Shahanoor Akter Chowdhury; Thomas McHale; Ranit Mishori; Ranit Mishori; Dahlia Fateen; Nima Sheth (Frontiers in Public Health)
BackgroundIn August 2017, the Rohingya population of northern Rakhine State in Myanmar fled to Bangladesh following “clearance operations” by the Myanmar security forces that were characterized by widespread and systematic violence, constituting severe human rights violations. The “clearance operations” were preceded by years of consistent denial of the human rights of the Rohingya people in Myanmar. This study examines the impact of these human rights violations on the trauma experiences of Rohingya survivors, their resulting mental health, and the availability and access to post-migration mental health services.MethodsQualitative one-on-one interviews were conducted with 26 health care professionals who cared for Rohingya refugees after their arrival in Bangladesh.ResultsTrauma experienced by the Rohingya spanned the period before, during, and following migration and was ongoing at the time of data collection. The impact of Rohingya survivors’ concurrent grief and trauma in relation to the violence they experienced in Myanmar as well as during and after their journey to Bangladesh that, at times, exacerbated survivors’ trauma presentation. There were limited mental health services available in Bangladesh and additional structural and procedural barriers to care that limited responsiveness to Rohingya survivors’ mental health needs.ConclusionThe Rohingya experienced traumatic human rights violations in Myanmar that led to their forced migration to Bangladesh. The Rohingya continued to experience trauma during their forced migration to Bangladesh and were exposed to additional stressors in the post-migration settings in refugee camps, including lack of access to adequate mental health services. These experiences have resulted in a spectrum of stress-and trauma-related symptoms. These findings show the mental health impact of protracted human rights violations on the Rohingya, revealing how trauma is not a singular event but a continuous experience. Detailing the limited mental health infrastructure and structural barriers facing Rohingya refugees in Bangladesh, the findings underscore the urgent need for trauma-informed interventions that address the complex psychological consequences of systemic violence and displacement. The findings emphasize the critical importance of holistic mental health support in refugee settings, providing evidence-based recommendations for the public health and humanitarian sector to consider when designing programs to address the mental health and psychosocial support needs of sexual violence survivors living in conditions of displacement.